The vascularized periosteum flap as novel tissue engineering model for repair of cartilage defects - Harhaus-Wähner, Leila; Huang, Jung-Ju; Kao, Shu-Wei; Wu, Yen-Lin; Mackert, Gina A.; Höner, Bernd; Cheng, Ming-Huei; Kneser, Ulrich; Cheng, Chao-Min (Journal of cellular and molecular medicine, 2015)
Periosteum is a promising tissue engineering scaffold in research of cartilage repair; so far however, periosteum transfers have not been realized successfully because of insufficient nourishment of the graft. In a translational approach we, for the first time, designed a vascularized periosteum flap as ‘independent’ biomaterial with its own blood supply to address this problem and to reconstruct circumscript cartilage defects. In six 3-month-old New Zealand rabbits, a critical size cartilage defect of the medial femur condyle was created and covered by a vascularized periosteum flap pedicled on the saphenous vessels. After 28 days, formation of newly built cartilage was assessed macroscopically, histologically and qualitatively via biomechanical compression testing, as well as on molecular biological level via immunohistochemistry. All wounds healed completely, all joints were stable and had full range of motion. All flaps survived and were perfused through their pulsating pedicles. They showed a stable attachment to the bone, although partially incomplete adherence. Hyaline cartilage with typical columnar cell distribution and positive Collagen II staining was formed in the transferred flaps. Biomechanical testing revealed a significantly higher maximum load than the positive control, but a low elasticity. This study proved that vascularization of the periosteum flap is the essential step for flap survival and enables the flap to transform into cartilage. Reconstruction of circumscript cartilage defects seems to be possible. Although these are the first results out of a pilot project, this technique, we believe, can have a wide range of potential applications and high relevance in the clinical field.